Head and neck lymphomas: a 20 year retrospective review of cases diagnosed in an oral pathology unit, Johannesburg, South Africa - Alli, Nasreen (My University, 2016)
Introduction: Lymphomas are the most frequent non-epithelial oral and maxillofacial malignancy. Non-Hodgkin lymphoma (NHL), though not common in the oral cavity is reported with increasing frequency in patients with human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS). An increased risk of lymphoma development is also seen in persons with primary immunodeficiency and connective tissue diseases and patients on cytotoxic immunosuppressive treatment. With South Africa looming as a country with the highest incidence of HIV and AIDS worldwide, an epidemiologic study would provide valuable insight into head and neck lymphomas in a defined South African population. Aim: This retrospective review is aimed at evaluating the frequency and clinico-pathologic characteristics of patients diagnosed with head and neck lymphoma at the Department of Oral Pathology, University of the Witwatersrand, Johannesburg over the 20 year period, 1993-2012. Methods: Histopathology reports of patients diagnosed with lymphomas of the head and neck were reviewed. Epidemiological data including the demographic, clinical, laboratory, and histological parameters for each patient were recorded. Variables included, amongst others age, gender, site, size of tumour, histologic subtype of lymphoma and year of diagnosis. Lymphomas were classified according to the 2008 World Health Organisation classification of tumours of lymphoid neoplasms. Results: There were 504 patients (2.24%) with head and neck lymphomas. The median age was 39 years and the age range was 2 to 100 years. The male:female ratio was 1.13:1. The cervical lymph node was the most common anatomic site (115 cases) and the maxilla (60 cases) was the most common extranodal site. Plasmablastic lymphoma (159 cases) was the most common histologic subtype followed by diffuse large B-cell lymphoma (155 cases). The most common Hodgkin’s lymphoma (HL) was nodular sclerosing HL (21 cases). Ninety percent of cases were NHLs and ten percent were HL. Seventy-three percent of cases were extranodal and twenty-seven percent were nodal in origin. A mass/swelling was found to be the most common clinical feature and B symptoms only occurred in one patient. Conclusion: This study confirmed the increase in head and neck lymphoma frequency over the 20 year period, contrary to that found in Western countries, which show a decline in incidence with highly active antiretroviral therapy. Oral and maxillofacial lymphomas occurred predominantly in the third decade with a strong male bias. Most were extranodal, presenting as ulcerated painful swellings. This study serves as a baseline for future head and neck lymphoma studies, especially in a South African setting.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry in the branch of Oral Pathology Johannesburg, March 2016
Keywords: Head and Neck Lymphomas; Lymphoma; HIV